2010
DOI: 10.1111/j.1600-0404.2009.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes and place of death in Italian patients with amyotrophic lateral sclerosis

Abstract: The leading cause of death in ALS remains the respiratory failure, followed by the sudden death and death during sleep. Most patients in our cohort died at home, a choice that might be only partially driven by cultural factors. These findings might have a great impact on the development of the advanced and end-of-life palliative care and in the planning of specialized care services, as hospice and nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 27 publications
5
54
1
1
Order By: Relevance
“…A question arises of why, besides the establishment of mainly clinically-based criteria for the diagnosis of ALS [6] and the spread of information about the disease, the diagnostic delay is still about one year, that is nearly one-third of the natural history of the disease [1]. Furthermore, being first observed by a neurologist does not seem to shorten the diagnostic delay.…”
Section: Independent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…A question arises of why, besides the establishment of mainly clinically-based criteria for the diagnosis of ALS [6] and the spread of information about the disease, the diagnostic delay is still about one year, that is nearly one-third of the natural history of the disease [1]. Furthermore, being first observed by a neurologist does not seem to shorten the diagnostic delay.…”
Section: Independent Variablementioning
confidence: 99%
“…Death usually occur within 3-5 years after onset, the main cause being the respiratory failure [1]. Although the established pharmacological therapy for ALS, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the use of NIV in ALS patients, and have documented benefits on survival and quality of life [9,14,21]. Recent evidence shows the need to improve comfort and synchrony for a better NIV compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Others variables beyond number of hours/day, namely the ventilation settings of NIV equipment, need be evaluated about their potential role on functional and survival outcomes, and it has never been published. In addition, recent studies have suggested other causes of death in ALS [6][7][8][9][10][11], which reinforces the need to clarify whether respiratory disturbances and discomfort with NIV are present near the time of death, and whether they could possibly be amenable to corrections. We aimed to investigate the prognostic factors for functional decline among ALS patients under NIV, considering all variables recorded by the equipment software [12] from initial adaptation until to death or end of study.…”
Section: Introductionmentioning
confidence: 99%
“…Death frequently occurs within 3-5 years from onset, mostly because of respiratory failure (Spataro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%